2008
DOI: 10.1002/ejoc.200800422
|View full text |Cite
|
Sign up to set email alerts
|

Multicomponent Domino Reaction Promoted by Mg(ClO4)2: Highly Efficient Access to Functionalized 1,4‐Dihydropyridines

Abstract: An efficient, one‐pot multicomponent synthetic protocol toward substituted 1,4‐dihydropyridines from aromatic amines, β‐keto derivatives, and ethyl propiolate mediated by Mg(ClO4)2 is described. When ortho‐ or meta‐substituted arylamines are used, two conformational isomers are generated. An NMR spectroscopic study of the energy barrier involved in the interconversion of the isomers is reported.(© Wiley‐VCH Verlag GmbH & Co. KGaA, 69451 Weinheim, Germany, 2008)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…33 On the other hand, Sambri and coworkers developed an unconventional multicomponent protocol for the synthesis of 1,4-DHPs 47 from ethyl propiolate, two 1,3-dicarbonyl compounds and primary amines wherein ethyl propiolate served as electrophile (Scheme 20). 34…”
Section: Multicomponent Synthesis Of 14-dhps Using Amine As Amino Sourcementioning
confidence: 99%
“…33 On the other hand, Sambri and coworkers developed an unconventional multicomponent protocol for the synthesis of 1,4-DHPs 47 from ethyl propiolate, two 1,3-dicarbonyl compounds and primary amines wherein ethyl propiolate served as electrophile (Scheme 20). 34…”
Section: Multicomponent Synthesis Of 14-dhps Using Amine As Amino Sourcementioning
confidence: 99%
“…The latter reaction has been already mentioned in section , Scheme being part of the multistep synthesis of 1,8-dioxo-octahydroxanthenes. The former is a natural extension of our work already described in the same section (Schemes and ). The use of Mg(ClO 4 ) 2 (10 mol %) and of MgSO 4 (20 mol %) as water scavenger allows the Knoevenagel condensation of aliphatic and aromatic aldehydes with β-diketones and β-ketoesters without any traces of byproduct in 55−88% yields.…”
Section: Miscellaneousmentioning
confidence: 76%
“…In fact, the reaction of enamino esters with ethyl propiolate does not give the expected pyridone, but a dihydropyridine 161 derived from a double conjugate addition of enamino derivative 160 to propiolate, followed by an intramolecular condensation with elimination of amine (Scheme 107). 305 The reaction was tested with differently substituted anilines (39-95% yield), and electron-donating substituents had no effect on the yields whereas a decrease with weak deactivating group was observed. Hindered amines lead to increasing amounts of side product 162, and in particular, 2-tertbutylaniline gives exclusively 162.…”
Section: Six-membered Ringsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Wang and co-workers [26] have reported the three-component synthesis of 1,4-DHPs employing electron deficient alkynes (alkyl propiolates), primary amines and salicylaldehydes with the catalysis of TFA, but using other aryl aldehydes rather than salicylaldehyde has been found not applicable because of the indispensable activation effect of hydroxyl group. [41] In the type of 1,4-DHPs synthesis involving aldehydes, propiolates and amines, the key factor is the formation of enaminoester intermediates via the addition of amines to propiolates. On the other hand, Jiang and co-workers [29] have found that L-proline catalyzes the multicomponent reactions of acyclic 1,3-dicarbonyl compounds, aldehydes, amines and alkynes to yield also 1,4-DHPs, and the three-component synthesis of polysubstituted 1,4-DHPs involving primary amines, dialkyl acetylenedicarboxylates and methyl (arylmethylidene) pyruvates has been recently achieved.…”
Section: Introductionmentioning
confidence: 99%